Development of a Transient Model for Evaluation of Shell and Tube Heat Exchanger with Helical Baffles Applied for SiO2 Nanofluid - M.L. Magalhães; A.S. Pereira; S.J.M. Cartaxo (Journal of Advanced Thermal Science Research, 2018)
While integrated sizing and analysis procedures for helical shell-and-tube heat exchangers are available in the technical literature, the same does not hold for differential transient methods. This work aims to develop a differential transient model for a shell-and-tube heat exchanger with helical baffles with one pass in the shell and two passes in the tubes, considering one-dimensional variation along the length of the equipment. It is intended to determine the fluids temperature profiles and overall heat transfer coefficient along the equipment. Temperature correction factor Ft, heat load and pressure losses were estimated with the model. The thermophysical properties of the fluids were locally evaluated by using published predictive correlations. Simulations were performed using Python framework computing environment assuming a SiO2 nanofluid.